DESIGN OF A WEB-BASED SALES AND STOCK INVENTORY INFORMATION SYSTEM AT BASUA COFFE - Alfina TiurMida Sitanggang; Ahmad Fadhil Afanda; Ade Suryani; Raspan Hamdi; Sunarsih Sunarsih; Putri Fatimah; Arifin Arifin (Smart Education, 2025)
Abstract: Basua Coffee is a culinary business facing challenges in managing sales and inventory, which are still done manually. This results in data discrepancies between recorded stock levels and actual conditions, delays in sales reporting, and potential transaction recording errors. The purpose of this study is to design and build a web-based sales and inventory information system that can improve operational efficiency and data accuracy at Basua Coffee. The research method used is a software engineering method with a waterfall approach, including the stages of needs analysis, system design, implementation, and testing. Data collection techniques were carried out through observation, interviews, and documentation studies. System analysis was carried out using UML (Unified Modeling Language) modeling, while system testing was carried out using the black box testing method. The results of this study indicate that the designed information system is able to automatically record sales transactions, monitor inventory in real-time, and produce accurate sales and stock reports. Thus, this system can assist management in making faster and more accurate decisions.Keyword: basua coffe; inventory; information system; sales.Â Abstract : Basua Coffee merupakan sebuah usaha kuliner yang menghadapi tantangan dalam mengelola penjualan dan inventaris yang masih dilakukan secara manual. Hal ini menyebabkan terjadinya ketidaksesuaian data antara tingkat stok yang tercatat dengan kondisi aktual, keterlambatan pelaporan penjualan, dan potensi kesalahan pencatatan transaksi. Tujuan penelitian ini adalah merancang dan membangun sistem informasi penjualan dan inventaris berbasis web yang dapat meningkatkan efisiensi operasional dan akurasi data di Basua Coffee. Metode penelitian yang digunakan adalah metode rekayasa perangkat lunak dengan pendekatan waterfall, meliputi tahapan analisis kebutuhan, perancangan sistem, implementasi, dan pengujian. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan studi dokumentasi. Analisis sistem dilakukan dengan pemodelan UML (Unified Modeling Language), sedangkan pengujian sistem dilakukan dengan metode pengujian black box. Hasil penelitian ini menunjukkan bahwa sistem informasi yang dirancang mampu mencatat transaksi penjualan secara otomatis, memantau inventaris secara real-time, dan menghasilkan laporan penjualan dan stok yang akurat. Dengan demikian, sistem ini dapat membantu manajemen dalam mengambil keputusan yang lebih cepat dan akurat.Keywords: basua coffe; inventaris; penjualan; sistem informasi.